Penerapan Algoritma Naive Bayes Untuk Diagnosa Penyakit Gagal Ginjal Kronis - Arim Nur Faddillah; Jeffry Wijaya; Riko Hidayat (Jurnal ICT : Information Communication & Technology, 2019)
Kidney is an organ that has a big role in filtering substances that enter the body. This can be seen in kidney function, which is excreting metabolic waste. Damage to the kidneys that cause damage to kidney function. One of the diseases of the kidney that cannot be treated is chronic kidney failure (Chronic Kidney Disease). Chronic kidney failure is difficult to know, certain methods are needed and it is not enough just by a medical examination. This study discusses the application of the Naif Bayes algorithm method for diagnosis or predict chronic kidney failure. This system is based on a dataset from Indian Chronic Kidney Disease (CKD) obtained from the UCI Machine Learning Repository website created in 2015.The results of this study get an accuracy of 91.25% for the 400 datasets tested.